The Police Diplomat Network as a response to Modern Challenges: A Portuguese Perspective. - Fernandes, Roberto Narciso Andrade (Estonian Academy of Security Sciences, 2024)
This research explores the transformation of international security dynamics amid the rising challenges posed by globalised crime and modern crises. A pivotal element in this discourse is the phenomenon of Russian irredentism, illuminating the territorial and geopolitical ambitions of a nation challenging established international norms. Within this evolving landscape, the concept of Police Diplomacy has taken on a new expression, marking a paradigmatic shift in which representatives of law enforcement agencies take on diplomatic functions previously reserved for politicians and career diplomats. Portugal’s Universalist orientation provides a compelling framework to contextualise this transition, reflecting the Nation’s commitment to universalist ideals and its active engagement in global collaborative efforts. Utilising Portugal as a focal point, this study offers an in-depth analysis of the police diplomat role, delineating its complexities, challenges, and implications within contemporary international relations. Throughout, emphasis is maintained on the overarching goal of peace diplomacy, centred on Human Security and the safeguarding of vulnerable populations.
Keywords: diplomacy; geopolitics; international cooperation; police liaison; security